Cervical spinal cord stimulation for the treatment of essential tremor. (1st August 2018) - Russo, Marc; Santarelli, Danielle M; Smith, Ushtana
Abstract : A patient with refractory essential tremor of the hands and head/neck refused deep brain stimulation and requested consideration for spinal cord stimulation (SCS). Trial of a cervical SCS system using a basic tonic waveform produced positive outcomes in hand tremor, head-nodding and daily functioning. The patient proceeded to implant and received regular programming sessions. Outcomes were recorded at follow-ups (1, 3, 6, 12, 23 months postimplant) and included patient self-reported changes, clinical observations, handwriting assessments and The Essential Tremor Rating Assessment Scale scores. Trial of a paraesthesia-free burst waveform programme produced a small improvement in head-nodding, without uncomfortable paraesthesias. With continued programming, the patient reported further improvements to tremor and functionality, with minimal tremor remaining at 12–23 months. No major side effects were reported.